Genetic diversity in grain quality and nutrition of aromatic rices - Shahidullah, S. M.; Musa, Mohamed Hanafi; Ashrafuzzaman, Muhammad; Ismail, Mohd Razi; Khair, A. (Academic Journals, 2009)
The study was conducted at Bangladesh Rice Research Institute (BRRI), Gazipur in 2005 to assess the genetic divergence of aromatic rices for grain quality and nutrition aspects. Forty genotypes composed of 32 local aromatic, five exotic aromatic and three non-aromatic rice varieties were used. Univariate and multivariate analyses were done. Enormous variations were observed in majority of characters viz. grain length, breadth, kernel weight, milling yield, kernel length, L/B ratio of kernel, volume expansion ratio (VER), protein content, amylose content, elongation ratio (ER) and cooking time. In multivariate analysis, genotypes were grouped into six clusters. In the discriminant function analysis (DFA), function 1 alone absorbed 61.7% of the total variance. The most contributing variables were kernel weight, kernel length and L/B ratio in function 1. The inter-cluster D2 value was maximum (26.53) between I and VI followed by 21.28 (between I and V). Minimum D2 value was found (5.90) between II and III. Majority of the local aromatic rice varieties with smaller kernels were included in the cluster I. The cluster III contains Elai, sarwati and sugandha-1 with long-slender kernel and ‘very good’ appearance. Thus, these varieties can be used in breeding programme for improvement of germplasms in cluster-I.